Analisis Wacana Pada "Bingkai" Majalah Suara Muhammadiyah Dan Implementasinya Sebagai Bahan Ajar Bahasa Indonesia Di SMA - Rohmani, Hidiyah; , Prof. Dr. Markhamah, M.Hum; , Drs. Yakub Nasucha, M.Hum (2013)
This study aims to describe the structure, social cognition, contexts of the discourse on the 'Bingkai' Suara Muhammadiyah magazine so the readers know and understand contain of the meaning in the discourse as well as the implementation of Indonesian teaching materials. This research is a qualitative approach to the critical analysis of Van Dijk models. The subject of this study is the menu 'Bingkai' of the magazine which published Dr. Haedar Nasir's writings. The conclusion is that the three research sample texts, have the macro structure /thematic different. The theme of texs 1 is to strangther character, while text 2 builds civilization, and text 3 is about the struggle of values. The superstructure /schematic, preliminary those text displays that contains a description of the problems in life are developed with the subtitle contains the concepts, examples, and the anticipation /solution. The micro structure of the texts includes the text contains semantic elements background, detailed, and intent. Among the texts used syntactic elements of lexicon which are almost same in the form of diction / word straight forward and there are some persuasive expression. Stylistic form of figure of speech paradox and satire is more dominant in among the texts. Social cognition, suggests that the text is an expression of the author who is associated with the establishment of Muhammadiyah ideology. Contexts analysis, describes the condition of the Indonesia people who have various problems. One of the reason is the weakening commitment especially Muhammadiyah members so it changes the values, outlook and attitude in life. Therefore, discourse of "Bingkai" is a means of understanding and reinforcement of the ideology. The writer hopes that can implements the results of the analysis as Indonesian teaching materials in speaking competence forhigh school students in the competence of expressing ideas, feedback, and information in a discussion.